Pengenalan Technopreneurship untuk Siswa Sekolah Menengah Kejuruan: Membangun Jiwa Wirausaha Berbasis Teknologi Digital di SMK Bintang Nusantara - Chairul Chairul; Ardijan Ardijan (PT Jurnal Cendekia Indonesia, 2025)
With the development of digital technology, Vocational High School (SMK) graduates must not only possess technical skills but also the ability to become entrepreneurs using technology. The purpose of this Community Service (PKM) activity is to teach SMK Bintang Nusantara students about the concept of technopreneurship. This is done to foster a digital entrepreneurial spirit from an early age. The implementation method includes counseling, interactive discussions, simple practices, and digital business planning simulations tailored to students' expertise. The material presented covers the basic concepts of technopreneurship, the use of digital technology in business, and examples of technology-based business opportunities relevant to vocational high school students. The results of the activity show an increase in students' understanding of technopreneurship and increased motivation to develop independent business ideas based on digital technology. Furthermore, students are highly engaged in the discussions and simulations carried out. This activity helps students become more creative, innovative, and independent. As part of increasing digital entrepreneurship in vocational education, such activities are expected to be carried out continuously.